GCKIII kinases control hepatocellular lipid homeostasis via shared mode of action - Emmelie Cansby; Mara Caputo; Emma Andersson; Rasool Saghaleyni; Marcus Henricsson; Ying Xia; Bernice Asiedu; Matthias Blüher; L. Thomas Svensson; Andrew J. Hoy; Margit Mahlapuu (Journal of Lipid Research)
Metabolic dysfunction–associated steatotic liver disease has emerged as a leading global cause of chronic liver disease. Our recent translational investigations have shown that the STE20-type kinases comprising the GCKIII subfamily—MST3, STK25, and MST4—associate with hepatic lipid droplets and regulate ectopic fat storage in the liver; however, the mode of action of these proteins remains to be resolved. By comparing different combinations of the silencing of MST3, STK25, and/or MST4 in immortalized human hepatocytes, we found that their single knockdown results in a similar reduction in hepatocellular lipid content and metabolic stress, without any additive or synergistic effects observed when all three kinases are simultaneously depleted. A genome-wide yeast two-hybrid screen of the human hepatocyte library identified several interaction partners contributing to the GCKIII-mediated regulation of liver lipid homeostasis, that is, PDCD10 that protects MST3, STK25, and MST4 from degradation, MAP4K4 that regulates their activity via phosphorylation, and HSD17B11 that controls their action via a conformational change. Finally, using in vitro kinase assays on microfluidic microarrays, we pinpointed various downstream targets that are phosphorylated by the GCKIII kinases, with known functions in lipogenesis, lipolysis, and lipid secretion, as well as glucose uptake, glycolysis, hexosamine synthesis, and ubiquitination. Together, this study demonstrates that the members of the GCKIII kinase subfamily regulate hepatocyte lipid metabolism via common pathways. The results shed new light on the role of MST3, STK25, and MST4, as well as their interactions with PDCD10, MAP4K4, and HSD17B11, in the control of liver lipid homeostasis and metabolic dysfunction–associated steatotic liver disease susceptibility.